2021
DOI: 10.1371/journal.pone.0251832
|View full text |Cite
|
Sign up to set email alerts
|

The petrosal and basicranial morphology of Protoceras celer

Abstract: Protoceratids are an extinct family of endemic North American artiodactyls. The phylogenetic position of protoceratids in relation to camelids and ruminants has been contentious for over a century. The petrosal morphology of basal (Leptotragulus) and derived (Syndyoceras) protoceratids has suggested that protoceratids are closely related to ruminants, whereas a prior description of a disarticulated intermediate protoceratid petrosal (Protoceras celer) indicated that protoceratids were closely related to cameli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(176 reference statements)
0
2
0
Order By: Relevance
“…Webb and Taylor (1980) reported that protoceratids—particularly Protoceras —have the same morphology as camelids, citing Flower (1885) and Scott (1895) as authorities. The atypical vertebrarterial canal morphology of camelids and protoceratids is the only synapomorphy uniting the two families (e.g., Joeckel and Stavas, 1996; Prothero, 1998a; Norris, 2000; Robson et al, 2021) and has been used as a character in numerous large-scale artiodactyl taxon-character matrices (e.g., Gentry and Hooker, 1988; Geisler and Uhen, 2003, 2005; Theodor and Foss, 2005; Geisler et al, 2007; Thewissen et al, 2007; Geisler and Theodor, 2009). Oddly, members of the Oromerycidae, the putative sister group to the Camelidae, retain the typical artiodactyl condition (Gentry & Hooker, 1988; Prothero, 1986, 1998b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Webb and Taylor (1980) reported that protoceratids—particularly Protoceras —have the same morphology as camelids, citing Flower (1885) and Scott (1895) as authorities. The atypical vertebrarterial canal morphology of camelids and protoceratids is the only synapomorphy uniting the two families (e.g., Joeckel and Stavas, 1996; Prothero, 1998a; Norris, 2000; Robson et al, 2021) and has been used as a character in numerous large-scale artiodactyl taxon-character matrices (e.g., Gentry and Hooker, 1988; Geisler and Uhen, 2003, 2005; Theodor and Foss, 2005; Geisler et al, 2007; Thewissen et al, 2007; Geisler and Theodor, 2009). Oddly, members of the Oromerycidae, the putative sister group to the Camelidae, retain the typical artiodactyl condition (Gentry & Hooker, 1988; Prothero, 1986, 1998b).…”
mentioning
confidence: 99%
“…The evolutionary position of Protoceratidae within Artiodactyla is ambiguous. Protoceratids may be closely related to camelids (Patton & Taylor, 1971, 1973Webb & Taylor, 1980) or ruminants (Gentry & Hooker, 1988;Joeckel & Stavas, 1996), but there are few derived features linking the family to either clade (Norris, 2000;Prothero & Ludtke, 2007;Robson et al, 2021Robson et al, , 2022. One of the most compelling arguments for a close evolutionary relationship between protoceratids and camelids is their unusual and supposedly shared vertebrarterial canal morphology (Webb & Taylor, 1980).…”
mentioning
confidence: 99%